Posttraumatic syringomyelia - Bhatoe, Harjinder S (Indian Journal of Neurotrauma, 2009)
Posttraumatic syringomyelia is an uncommon cause of late neurological deterioration in a patient with spinal cord injury. The pathology has received recent attention due to increased physician awareness and the availability of MR imaging. The underlying mechanism is probably local arachnoid scarring and obstruction to CSF flow, followed by seepage of CSF through the Virchow-Robin spaces. Persistent deformity predisposes to formation of posttraumatic syrinx. Anatomical decompression, division of arachnoid scarring, correction of spinal deformity and shunting procedures are measures to arrest the progress of the syrinx.
Keywords: spinal cord; spinal injury; syringomyelia